JUSTICE ISSUES IN BASIC HEALTH CARE AND THE CHALLENGE OF GENETIC MEDICINES: A Catholic Perspective for the Indian Context - Karuvelil, John (Asian Horizons, 2010)
The Christian commitment to health has inspired theologians and ethicists to reflect on the importance of health and provisions for health care for people. Today, even though health care has come to be considered a human right, millions across the world, especially in the developing and underdeveloped countries, have little or no access to an acceptable level of health care. Even a fast developing country like India with 1.2 billion people has over 421 million people under the poverty-line who have very little access to health care.